(3YHjQ GdJYHjQs - (3CHj GdeMGSf eMeO Hf YHO GdhgGH Hf TYHGf Hf OGhhO GdgePGfj GdcGXej,J (B1303 (3g` s
(3ChdgG (B:s
(3CWjH YHjQ jbPag YHGH GdLfGf, Edi ShGMd GdHjGf, aJahM QhGFMg aJYHb Hg CQOGf GdCQbGe WjHkG CeG HYO Ef ef eff Gddg JYGdi Ydqj Cf MHH GdYde Edqj s
(3BNQgG (B:s
(3aEPG CfUahG JYjf Cf ojKfj YdjgG PhGdHQ ef hdOgG gPG eG JjSQ GSJfSGNg ef cJGH YHjQ GdJYHjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B258 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B30 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs